Somaliland women’s perception of stillbirth - a descriptive survey study - Malm, Mari-Cristin; Osman, Fatumo; Ahmed Ibrahim, A.; Farah Hasan, H.; Erlandsson, Kerstin; Kiruja, J.; Kalucza, Sara (Somali Health Action Journal, 2021)
Background: Somali women, not only those living in Somaliland but also those living abroad as asylum seekers and refugees, are highly vulnerable in terms of perinatal health outcomes. Respectful and supportive care is critical for all women when stillbirth occurs and improving bereavement care and reducing the stigma that surrounds stillbirth are global priorities. Culturally- and context-specific approaches that build on an understanding of the needs of women giving birth to a stillborn baby, no matter where or why, are required. Objective: This study aims to investigate and analyze Somali women’s experiences of stillbirth, including their perceived reasons for losing their unborn baby, the premonitions they had before giving birth and their experiences of psychosocial support from healthcare professionals and relatives. Methods: A descriptive retrospective study was conducted at the Borama regional hospital in Somaliland. A study-specific questionnaire was developed that gathered personal information and data on topics related to women’s experiences of stillbirth. Women who had either experienced a stillbirth at the hospital or had been referred there after a stillbirth 2015 were approached and 75 women agreed to participate in the study. Results: Most of the women were multiparas and had experienced a previous stillbirth. Before having it confirmed that their baby was no longer alive most of the woman reported that they had felt no fetal movements and had a premonition that something was wrong. The most common perceived cause of stillbirth that the women reported was prolonged labour followed by a ‘big baby’. Thirty-three women (44%) felt it was important to know the cause of the stillbirth and eight reported feeling angry or disappointed (11 %) with the health care providers who assisted them during labour, birth, or post-partum, although 41 women (55%) were satisfied with their treatment. A third of the women blamed themselves for their stillbirth and a majority spoke to others about it. Conclusions: Our results show that women in Somaliland share similar perceptions of stillbirth as women in high income countries. This raises important implications for antenatal care and preventive interventions and stressed the need to respond to women’s concerns regardless of background, context or setting. A maternal healthcare approach that is equal in its global application must be established to enable health care providers to give relevant information and care both in the cultural setting of Somaliland and elsewhere in the world where Somali-born women live and give birth.